Skew-normal Regression for Determination of Risk Factors Associated with LBW - Seem, Kristoffer (My University, 2014)
In the last 20 years there has been no real decrease in infant mortality rate in the U.S. This is due to a general increase in the proportion of low birth weight (LBW) that have been born in more recent years. The purpose of this study was to give a more accurate depiction of the risk factors that are associated with low birth weight (LBW) infants in the U.S.
Color poster with text, images, and graphs.
Keywords: Low birth weight--United States; Risk factors; Posters